Recommendation framework: Improving automated collaborative filtering by trusted category - Noor, Md Sadaf (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.